Barriers and Facilitators to Cervical Screening among Migrant Women of African Origin: A Qualitative Study in Finland - Idehen Esther E; Pietilä Anna-Maija; Kangasniemi Mari (MDPI, 2022)
Globally, cervical cancer constitutes a substantial public health concern. Evidence recommends regular cervical cancer screening (CCS) for early detection of "precancerous lesions."Understanding the factors influencing screening participation among various groups is imperative for improving screening protocols and coverage. This study aimed to explore barriers and facilitators to CCS participation in women of Nigerian, Ghanaian, Cameroonian, and Kenyan origin in Finland. We utilized a qualitative design and conducted eight focus group discussions (FGDs) in English, with women aged 27-45 years (n = 30). The FGDs were tape-recorded, transcribed verbatim, and analyzed utilizing the inductive content analysis approach. The main barriers to CCS participation included limited language proficiency, lack of screening awareness, misunderstanding of screening's purpose, and miscomprehension of the CCS results. Facilitators were free-of-charge screening, reproductive health services utilization, and women's understanding of CCS's importance for early detection of cervical cancer. In conclusion, among women, the main barriers to CCS participation were language difficulties and lack of screening information. Enhancing screening participation amongst these migrant populations would benefit from appropriate information about the CCS. Those women with limited language skills and not utilizing reproductive health services need more attention from healthcare authorities about screening importance. Culturally tailored screening intervention programs might also be helpful.